Reduction of Blackout Periods in GRA Arrangements. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
In the context of the March 2009 reforms of the General Resources Account (GRA) lending toolkit, the Executive Board asked staff to prepare a paper addressing the problem of blackout periods under GRA arrangements, which interrupt access to accumulated but undrawn purchases. This request arose in the context of the decision to make high-access precautionary arrangements (HAPAs) available to members on a more regular basis (with greater flexibility regarding frontloading of access). Blackout periods have important implications given that the crisis-prevention and confidence-enhancing role of precautionary arrangements (particularly HAPAs) depend on strong assurances that resources will be available if needed. Section II provides background on the issue of blackout periods and the expanded role of precautionary arrangements under the recent reforms. Section III proposes a solution to provide greater assurances to members regarding continuity of access to accumulated rights while maintaining appropriate safeguards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Blackout Period; Drawing Right; Period; PP; Test Data; Costa Rica